Recent Advances in the Study of Bipolar/Rod-Shaped Microglia and their Roles in Neurodegeneration - Au, Ngan Pan Bennett; Ma, Chi Him Eddie (Frontiers in Aging Neuroscience, 2017)
Microglia are the resident immune cells of the central nervous system (CNS) and they contribute to primary inflammatory responses following CNS injuries. The morphology of microglia is closely associated with their functional activities. Most previous research efforts have attempted to delineate the role of ramified and amoeboid microglia in the pathogenesis of neurodegenerative diseases. In addition to ramified and amoeboid microglia, bipolar/rod-shaped microglia were first described by Franz Nissl in 1899 and their presence in the brain was closely associated with the pathology of infectious diseases and sleeping disorders. However, studies relating to bipolar/rod-shaped microglia are very limited, largely due to the lack of appropriate in vitro and in vivo experimental models. Recent studies have reported the formation of bipolar/rod-shaped microglia trains in in vivo models of CNS injury, including diffuse brain injury, focal transient ischemia, optic nerve transection, and laser-induced ocular hypertension. These bipolar/rod-shaped microglia formed end-to-end alignments in close proximity to the adjacent injured axons, but they showed no interactions with blood vessels or other types of glial cell. Recent studies have also reported on a highly reproducible in vitro culture model system to enrich bipolar/rod-shaped microglia that acts as a powerful tool with which to characterize this form of microglia. The molecular aspects of bipolar/rod-shaped microglia are of great interest in the field of CNS repair. This review focuses on studies relating to the morphology and transformation of microglia into the bipolar/rod-shaped form, along with the differential gene expression and spatial distribution of bipolar/rod-shaped microglia in normal and pathological CNSs. The spatial arrangement of bipolar/rod-shaped microglia is crucial in the reorganization and remodeling of neuronal and synaptic circuitry following CNS injuries. Finally, we discuss the potential neuroprotective roles of bipolar/rod-shaped microglia, and the possibility of transforming ramified/amoeboid microglia into bipolar/rod-shaped microglia. This will be of considerable clinical benefit in the development of novel therapeutic strategies for treating various neurodegenerative diseases and promoting CNS repair after injury.